Do large herbivores select a diet that maximizes short-term energy intake rate? - van Wieren, S.E. (Forest ecology and management, 1996)
Using field data on diet composition, diet quality and eating behaviour of three species of herbivores (red deer, Highland cattle and Konik ponies) it was tested if herbivores select their diet according to the intake rate maximizing principle. The digestible organic matter intake rate (DOMIR) was used as test parameter. Across all species and diets, 61% of the diet composition could be explained by rate maximization, ponies having the lowest (52.1%) and red deer having the highest (72.1%) proportion of the highest DOMIR-preference class in their diet. Possible reasons for not selecting a perfect optimal diet in the sense of energy maximization include estimation errors, the lack of inclusion of nutrient constraints in the model, and the effects of living in a complex and constantly changing environment leading to ‘imperfect’ foraging decisions. Despite the imperfections, the results do lend substantial credit to the rate maximizing view.